A cat-bite wound infected with Vibrio Alginolyticus following use of sea cucumber oil - Mohamed N.A.; Joseph P.G.; Hussin H.; Hashim R. (SEAMEO TROPMED Network, 2024)
Vibrio alginolyticus is a halophilic gram-negative marine pathogen. The modes of transmission are mainly via direct contact with seawater and indirect contact through marine creatures. We report here a 28-year-old accountant diagnosed with right leg abscess after being bitten and scratched by a stray cat. Vibrio alginolyticus was isolated from the pus sample. The patient gave no history of contact with ocean water immediately before or after the cat scratch episode. The patient did apply commercial sea cucumber oil to the wound; we presume this is the cause of the Vibrio alginolyticus wound infection. To the best of our knowledge, this is the first reported case of Vibrio alginolyticus wound infection caused by commercially available sea cucumber oil.